2018
DOI: 10.1093/nar/gky743
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous single-strand DNA breaks at RNA polymerase II promoters in Saccharomyces cerevisiae

Abstract: Molecular combing and gel electrophoretic studies revealed endogenous nicks with free 3′OH ends at ∼100 kb intervals in the genomic DNA (gDNA) of unperturbed and G1-synchronized Saccharomyces cerevisiae cells. Analysis of the distribution of endogenous nicks by Nick ChIP-chip indicated that these breaks accumulated at active RNA polymerase II (RNAP II) promoters, reminiscent of the promoter-proximal transient DNA breaks of higher eukaryotes. Similar periodicity of endogenous nicks was found within the ribosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 131 publications
0
9
0
Order By: Relevance
“…Single-stranded DNA is exposed following fission yeast condensin inactivation [61], again dependent on active transcription [23]. Together with the observation of naturally occurring single-stranded DNA breaks at promotors of active genes and transcription-dependent promoter decompaction [62,63], this highlights the challenge to genome stability that arises from DNA unwinding and topological strain associated with gene transcription. To understand how condensin conveys its protective effect, it will be important to map locations of preferential condensin binding in the interphase nucleus, as well as the locations of the fragile sites where DNA breaks in its absence.…”
Section: Discussionmentioning
confidence: 99%
“…Single-stranded DNA is exposed following fission yeast condensin inactivation [61], again dependent on active transcription [23]. Together with the observation of naturally occurring single-stranded DNA breaks at promotors of active genes and transcription-dependent promoter decompaction [62,63], this highlights the challenge to genome stability that arises from DNA unwinding and topological strain associated with gene transcription. To understand how condensin conveys its protective effect, it will be important to map locations of preferential condensin binding in the interphase nucleus, as well as the locations of the fragile sites where DNA breaks in its absence.…”
Section: Discussionmentioning
confidence: 99%
“…This work also illuminates novel aspects of function of Top1. Though it was reported that Top1 associates with active RNA polymerase to relieve DNA supercoils generated in the process of transcription (41)(42)(43), our data suggests that Top1 can also functions in a transcription-independent relief of supercoils since a majority of mutations was seen in heterochromatin (H3K9me3 and H3K27me3 patterns, see Fig. S2).…”
Section: Discussionmentioning
confidence: 61%
“…7) shifted back the stability of the H3K4me3 nucleosomes to those of the control, showing that topoisomerase II was in place and potentially active, but rendered inactive in the absence of KDM4 or without the enzymatic activities involved. The decrease of nicks upon KO induction was also analyzed in an experiment when the overall nick levels were studied by a reverse Southwestern (rSW) blot procedure 55 , as shown in Suppl. Fig.…”
Section: Resultsmentioning
confidence: 99%